Dynamics of T- and B-lymphocytes in patients with rheumatoid arthritis, receiving biological disease-modifying antirheumatic drugs - A. V. Martynova; T. V. Popkova; A. P. Aleksankin; G. I. Gridneva; E. V. Gerasimova; Yu. N. Gorbunova; A. M. Lila (Современная ревматология)
Objective: assessment of the dynamics of T- and B-lymphocytes subpopulations in rheumatoid arthritis (RA) during therapy with synthetic disease-modifying antirheumatic drugs (sDMARDs) and biological disease-modifying antirheumatic drugs (bDMARDs): inhibitors of tumor necrosis factor α (iTNFα) and an inhibitor of interleukin 6 receptors (iIL6R ).Patients and methods. The study included 77 patients with RA who met the 2010 ACR/EULAR criteria (mean age 56 [44; 62] years). Group 1 included 30 (27 women and 3 men) patients with early RA who had not previously received therapy. Group 2 included 20 (14 women and 6 men) patients on sDMARD therapy who were prescribed iTNFα for the first time. The 3rd group is represented by retrospective data of 27 (23 women and 4 men) patients who previously used sDMARDs (MT – 85%, leflunomide – LEF – 15%), in whom iIL6R therapy was initiated for the first time. All study participants initially and 6 months later underwent immunophenotyping of T- and B-lymphocytes by flow cytofluorometry according to the standard method.Results and discussion. In all groups, there were no significant changes in the studied T-lymphocyte profile during 6 months of follow-up. When comparing the immunogram data of patients treated with sDMARDs and iTNFα, no significant differences in subpopulations of B-lymphocytes were found. At baseline, the iIL6R group had higher levels of naive B-lymphocytes and plasmablasts and low concentrations of «switched» B-cells. For all methods of treatment, the number of «switched» B-cells decreased, while plasmablasts and plasma cells increased.Conclusion. From the data obtained, it follows that the simultaneous decrease in the levels of memory B-cells and their «switched» forms, plasmablasts and plasma cells can be used as a marker for the early administration of drugs that disrupt the differentiation of B-lymphocytes, in particular, iIL6R.